Analisis Strategi Pembelajaran PAI Multikultural dalam Menumbuhkan Toleransi - Zahrah Nurkarimah; Dika Tripitasari; Ahdar Ahdar (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2026)
This study aims to analyze the strategies of multicultural Islamic Religious Education (PAI) learning in fostering students’ tolerance attitudes in the context of Indonesia’s diverse society. This research employs a qualitative approach using a library research method by examining various relevant scientific literatures, including journals, books, and policy documents. Data were analyzed through stages of data collection, reduction, thematic analysis, and synthesis. The findings indicate that there are three main strategies in implementing multicultural-based PAI learning: (1) enrichment of teaching materials with multicultural perspectives, (2) application of dialogic discussion and cooperative learning methods, and (3) creation of a democratic and inclusive school culture. These strategies are proven to significantly contribute to the development of students’ tolerance, inclusivity, and respect for diversity. However, several challenges are identified, such as limited teacher competence, lack of inclusive teaching materials, social pressures, and the influence of digital media. In conclusion, multicultural-based PAI learning plays a crucial role in shaping tolerant and inclusive students. Its successful implementation requires a holistic, adaptive, and collaborative approach involving curriculum development, teacher competence enhancement, and support from the broader educational ecosystem.